PENERAPAN PEMBUATAN RHIZOKOMPOS BAGI KELOMPOK WANITA TANI TUNAS HARAPAN KELURAHAN LIMAU MANIS KECAMATAN PAUH KOTA PADANG - Yulmira Yanti; Hasmiandy Hamid; Nurbailis Nurbailis; Noveriza Hermeria (LPPM Universitas Andalas, 2022)
The Tunas Harapan Women Farmers Group, Limau Manis Village, Pauh District, Padang City is one of the farmer groups that has various problems such as drought, high amount of unused land and arid land. The main crop planted during the rainy season is lowland rice, but most of the land becomes idle land during the dry season. Another problem that is often faced during the implementation of cultivation is the problem of soil quality, the lack of organic matter in the soil can also be the cause of degradation which has an impact on decreasing the productivity of rice plants. In terms of fertilization, farmers in this location still use artificial fertilizers (chemical fertilizers), where the use of chemical fertilizers can also reduce the quality of agricultural food so that it is not safe for consumption. The purpose of this activity is to increase public knowledge that corncob waste and cocoa waste that are widely available in the surrounding environment can be used as compost material. The method used is the method of socialization, counseling and discussion as well as demonstrations in the form of the practice of making rhizocompost directly in the field with farmer groups and the surrounding community. The results of this activity obtained rhizocompost made from corn cobs waste and cocoa waste. The conclusion that can be drawn from this activity is the increasing understanding of the community, especially the Farmers Group (KWT Tunas Harapan) about the benefits of corncob waste and cocoa waste that can be used as the main ingredients for making compost.